It's about time : the architecture of climate change. - Loorbach, Derk, ....-; Patteeuw, Véronique, ....-; Szacka, Léa-Catherine, ....-; Veenstra, Peter, 1980- (Rotterdam : Nai010 publishers, 2024)
This publication reveals time as a crucial but overlooked aspect in designing sustainable futures. Bridging past, present, and future, it presents historical and contemporary projects such as solar houses, autonomous structures, and earth buildings alongside dozens of key moments in environmental history, like the first Earth Day and the European Green Deal. The book intertwines climate action and architectural design, examining experiments in the past and the current transition, while offering hopeful glimpses of the future. The message is urgent: the momentum to realise change has arrived, and the architectural field is poised to play an important role in the time ahead.
Publicatie n.a.v. de tentoonstelling te Rotterdam tijdens de International Architecture Biennale Rotterdam van 22 september tot 13 november 2022
Keywords: Architectuur; Klimaat